ADSORPTION ON OXIDE SURFACES - STRUCTURE AND DYNAMICS - Libuda, Jörg; et al. (ELSEVIER SCIENCE BV, 1994)
In contrast to metal surfaces, oxide surfaces have only been studied rather recently with surface science methods. We report on the preparation and electron spectroscopic investigations of thin, well ordered surfaces of clean, adsorbate covered and modified oxide films. We identify surface excited states of a NiO(100) surface via electron energy loss spectroscopy in the regime of electronic excitations. Adsorption on well ordered terraces and on defects can be distinguished by choosing proper probe molecules. As a model system to study the structure and reactivity of an oxide supported ultrathin metal film we have deposited Pt onto a thin Al2O3(111) film grown on a NiAl(110) substrate. CO adsorption and low temperature dissociation in contrast to the bulk Pt has been observed.